2000
DOI: 10.1152/physiolgenomics.2000.2.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Reverse genetics in zebrafish

Abstract: The zebrafish has become a popular model system for the study of vertebrate developmental biology because of its numerous strengths as a molecular genetic and embryological system. To determine the requirement for specific genes during embryogenesis, it is necessary to generate organisms carrying loss-of-function mutations. This can be accomplished in zebrafish through a reverse genetic approach. This review discusses the current techniques for generating mutations in known genes in zebrafish. These techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…These cultures were not able to be maintained long enough to allow for gene transfer and cell selection for targeted gene insertion, but further elaboration of this technology may eventually lead to the ability to target specific genes for disruption as in the mouse. In the mean time, morpholinos provide a reliable method of transient gene "knockdown", and reverse genetics can still be accomplished by screening for randomly induced mutations affecting genes of interest (Appel et al, 1999;Lekven et al, 2001; reviewed in Lekven et al, 2000).…”
Section: Transgenic Techniquesmentioning
confidence: 99%
“…These cultures were not able to be maintained long enough to allow for gene transfer and cell selection for targeted gene insertion, but further elaboration of this technology may eventually lead to the ability to target specific genes for disruption as in the mouse. In the mean time, morpholinos provide a reliable method of transient gene "knockdown", and reverse genetics can still be accomplished by screening for randomly induced mutations affecting genes of interest (Appel et al, 1999;Lekven et al, 2001; reviewed in Lekven et al, 2000).…”
Section: Transgenic Techniquesmentioning
confidence: 99%
“…The Dfw8 mutation was induced by γ irradiation (Lekven et al, 2000;Lekven et al, 2001). Embryos were developed in an incubator at 28.5°C in water containing 0.008% Instant Ocean salts.…”
Section: Strains and Developmental Conditionsmentioning
confidence: 99%
“…The val b337 mutation was induced in the AB strain with ENU and is thought to be a null allele (Moens et al, 1996). The Df(LG23)wnt1 w5 deletion (herein referred to as Df w5 ) was induced by gamma-irradiation and identified in a polymerase chain reactionbased screen for loss of wnt1 (Lekven et al, 2000). Subsequent mapping showed that Df w5 removes 500 kb or less of LG 23, including the closely linked wnt10b locus (Lekven et al, 2003).…”
Section: Strains and Developmental Conditionsmentioning
confidence: 99%